The effect of green tea consumption on cholesterol reduction: a study among social service employees in East Nusa Tenggara - Patricia Flamli Uma Mukin; Anita Lidesna Shinta Amat; Elisabeth Levina Sari Setianingrum; Magdarita Riwu (Acta Biochimica Indonesiana, 2024)
Background: Hypercholesterolemia is a major risk factor for cardiovascular diseases, with elevated cholesterol levels prevalent in Indonesia. While pharmaceutical treatments are effective, they can be costly and cause side effects, prompting interest in natural remedies. Green tea, rich in bioactive compounds such as catechins, has shown potential in reducing cholesterol levels through its lipid-lowering and antioxidant properties. Objective: This study aimed to evaluate the effect of green tea consumption on total cholesterol levels in employees of the Social Service Office, East Nusa Tenggara Province, Indonesia. Method: An experimental study was conducted involving 38 participants aged 25–55 years, divided into a treatment group (n = 19) and a control group (n = 19). The treatment group consumed 240 ml of green tea twice daily for one week, while the control group received no intervention. Total cholesterol levels were measured using capillary blood and cholesterol test strips pre- and post-intervention. Data analysis was performed using the paired t-test. Results: The treatment group exhibited a significant reduction in total cholesterol levels (mean pre-treatment: 210.95 mg/dL; post-treatment: 188.26 mg/dL; p = 0.003). The control group showed no significant change (pre-treatment: 208.11 mg/dL; post-treatment: 214.37 mg/dL; p = 0.42). Conclusion: Green tea consumption for one week significantly reduced total cholesterol levels, demonstrating its potential as a natural remedy for managing hypercholesterolemia.